PEMIKIRAN FILOSOFIS PENDIDIKAN ISLAM (ESENSIALISME) - Ferizal Rachmad; Amril (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
This study aims to discuss philosophical thought of Islamic education (essentialism).. This research is a library research, namely research that originates from library materials using a qualitative approach. The results of the study show that essentialism is a philosophical school that wants humans to return to old culture. There are several advantages and disadvantages of essentialism, namely: a) Essentialism helps to return subject matter to the educational process, but does not support perennialism. that the true subject matter is the eternal reality presented in the great books of western civilization, b) the Great Book can be used but not for themselves but to be related to current realities, and c) change is a unchangeable reality in social life. The weaknesses are a) schools are not allowed to influence or determine social policies, b) essentialist thinkers generally do not have a unified line because they are guided by different philosophies, and c) the teacher's role is very dominant as someone who controls the field, and is a model very good. The general views of essentialist philosophy, namely: a) Ontological views (reality), b) Epistemological views (views of knowledge), c) Axiological views (views of values), and d) Views on education.